Spectrum of histopathological lesions in the fallopian tubes - Gon, S; Basu, A; Majumdar, B; Das, TK; Sengupta, M; Ghosh, D (Journal of Pathology of Nepal, 2013)
Background: Fallopian tubes are common surgical specimen in the pathology laboratory; still there is a lack of data to describe the frequency of various histological fi ndings. The aim and objectives of this study was to describe the various histopathological fi ndings of fallopian tubes. Materials and Methods: Two thousand fi ve hundred and seventy fi ve cases where fallopian tubes were removed either separately or along with other female genital tract organs were studied retrospectively and their histopathological fi ndings documented. Results: Ectopic pregnancy comprised maximum number of cases closely followed by salpingitis. Primary neoplastic lesions were rare as compared to secondary malignancies. Serial sections of fallopian tube and sections from representative areas are essential for a pathologist so that the diagnosis of these pathological entities is not missed. Conclusion: Though the fallopian tubes remain unremarkable in majority of the surgical pathological specimens, it must be subjected for histopathological examination to demonstrate the pathological lesions. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 356-360 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7858